Proses resiliensi jurnalis radio 68H pasca bom buku 15 Maret 2011 - Soerjoatmodjo, Gita W. L. (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2013)
On March 15, 2011, a bomb glued to a book and received by 68H News Agency (68H) exploded, causing severe injury to a police oficer on duty. Yet the journalists resumed work, advocated their stance for freedom of expression and continued broadcasting. Resilience, a successful adaptation to adversity to â€œbounce backâ€ is shown in this incident by 68H journalists and is relevant to any journalists working in Indonesia as one of the ive deadliest countries in 2010 according to Committee to Protect Journalists. Using semi-structured interview and â€˜resilience-as-a-processâ€™ perspective, this research describes how 68H journalists undergo their process, what occurs as they become resilient, resources they utilize, and consequent changes in their ability to maintain their resilience in the future. Results show that regrouping and capacity building are pivotal in the stages of their resilience process. It concludes that collective identity and leadership, in perceiving â€˜usâ€™ versus â€˜themâ€™ and in promoting values important to them, as well as social supports and shared experiences of past successes, are main resources of their resilience. Lessons learned from their error of judgement of threat assessment leads to changed attitude and security reinforcement that contribute to their future resilience.